Hide and seek - Mlynowski, Sarah; Myracle, Lauren, 1969-; Jenkins, Emily, 1967- (New York : Scholastic Press, 2020)
When a flood forces Nory and her best friends to evacuate Dunwiddle and relocate to prestigious Sage Academy, the upside-down magic students have a hard time fitting in.
3-6
4.4
Keywords: Magic -- Juvenile fiction; Belonging (Social psychology) -- Juvenile fiction; Friendship -- Juvenile fiction; Shapeshifting -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Magic -- Fiction; Belonging (Social psychology) -- Fiction; Friendship -- Fiction; Shapeshifting -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Fantasy fiction